New record of the rare alien grapsoid crab Percnon affine (H. Milne Edwards, 1853) (Crustacea, Decapoda, Grapsoidea, Plagusidae) from the northern Indian Ocean. (25th June 2015) - Naderloo, Reza; Fatemi, Yaser
Abstract : A large well-established population of the grapsoid crab Percnon affine (H. Milne Edwards, 1853) was observed in the rocky low-intertidal zone of Chabahar Bay, along the Iranian coasts of the Gulf of Oman. This is the first record of P. affine from the northern Indian Ocean.